HUBUNGAN DUKUNGAN SOSIAL KELUARGA DAN POLA KOMUNIKASI KELUARGA DENGAN TINGKAT DEPRESI LANSIA DI KELURAHAN PEKAYON JAYA BEKASI SELATAN - Mustofa, Sarah Nurul Izzah (2021)
The elderly often experience changes in their bodies with age, namely physical, psychological and social changes. Psychological conditions that can cause depression in the elderly can be influenced by family support and communication patterns that occur in the family. The purpose of this study was to determine the relationship between family social support and family communication patterns with the level of depression in the elderly in Pekayon Jaya Village, South Bekasi. This type of research is quantitative descriptive analytic method with a cross-sectional research design. The sampling technique used in this study was stratified random sampling and accidental sampling. The results of the chi square test analysis with a p value of 0.023 <0.05 for the variable of family social support with depression levels in the elderly. In the variable of family communication patterns with the level of depression in the elderly, the results obtained p value 0.000 <0.05. The results of this analysis show that there is a relationship between family social support and family communication patterns with the level of depression in the elderly in Pekayon Jaya Village, South Bekasi. So from the results of this study, it is hoped that the elderly will be more open with their families and families should pay more attention to the physical and psychological conditions of the elderly so that the elderly avoid depression.